Sistem Pakar Pengenalan Penyakit Kucing Berbasis Android Menggunakan Metode Naive Bayes - Angga Arian; Ria Arafiah; Muhammad Eka Suryana (Universitas Negeri Jakarta, 2023)
The animal that is currently being studied a lot is the cat, because there has been a lot of research related to this cat and it is easy to learn. This cat research also needs an expert or experts who can study this, especially cat diseases. This thesis research is aimed at the need for the public to know cat disease which is then applied in the form of an Android-based expert system application. Making this application of an expert system for recognizing cat diseases uses a method that is often used and studied by many people, namely the Naïve Bayes method. The purpose of making this cat disease recognition expert system is to help users, especially cat lovers, to get information about recognizing and treating their pets at an early stage when they have problems with their health so that they can recover faster from their illness. The results of the expert system research on the introduction of cat diseases, namely this application is used to determine the cat's disease suffered from the symptoms that have been described in the application and these symptoms are obtained directly from interviews from the two doctors (experts). The test also got good results, namely 100%.